Selecting health measurement scales: basic issues for considerations - Srisurapanont, Manit (Biomedical Sciences and Clinical Medicine, 2017)
At present, people have more needs on health. It is, therefore, necessary for medical professionals to elaborately measure or evaluate health. Health measurement scales for evaluating health abstract outcomes, eg, beliefs, feeling, attitudes, and behavior, has been more and more involved in health assessment. Health professionals, therefore, need competency in selecting health measurement scales, including the feasibility and costeffectiveness of assessment. In doing so, they will be able to convert such abstract outcomes into scores, which can be further computed and communicated. This article describes key issues for consideration in applying health measurement scales in clinical practice or research. Scale users should, fi rstly, consider the scale overview and, then, apply the classical test theory to determine the scale reliability and validity. Knowledge on item response theory can be additionally used with classical test theory and will be helpful to determine item properties. After all properties are taken into account, scale users would be able to choose the scales appropriate for their work.